LEGAL ASPECTS OF BUSINESS COMPETITION IN RELATION TO THE MECHANISM OF PREVENTING BANKING INDUSTRY TENDER CONSULTATIONS IN INDONESIA - Althaf Vidaro, Radhika; Gultom, Elisatris; Suparto, Susilowati (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2023)
Everyone wants a decent life for himself and those around him, and the state has the responsibility to provide for the welfare of its people, as stated in the 1945 Constitution.This study aims to examine the role of banking institutions in the welfare of society and support national development in Indonesia. In the 1945 Constitution, Article 33 has stipulated that economic development must achieve social justice for all people through a welfare approach and market mechanisms. The concept of economic democracy emphasizes the importance of the prosperity of society as a whole, and the principle of welfare is also recognized in Pancasila and social welfare laws. However, despite having a strategic role in the welfare of the people and supporting national development, the banking industry in Indonesia is often involved in law violations such as corruption. and collusion. These practices can hinder economic growth and equity at the national level. One example of a violation that often occurs is bid rigging in the banking industry, which harms the public interest and violates the principle of fair business competition. This research also highlights the importance of efforts to prevent and take action against these violating practices. These steps are important to ensure the continuity of fair business competition and to build public trust in the government and related institutions. In this context, this study presents an analysis of the efforts that have been made and recommendations for improving law enforcement and preventing corruption in the banking industry.